Rational Emotive Therapy untuk Remaja Berpikiran Negatif: Elaborasi Doktrin QS At-Tin : 4 - Ahmad Putra (Institut Agama Islam Negeri Bengkulu, 2020)
This study explains the efforts of rational emotive therapy in dealing with adolescent negative thoughts about their body which are not ideal, which in the end he considers that their body shape prevents their desire to achieve their ideals as a member of the police force. The client feels hopeless and disappointed because his body is not ideal to be able to become a police officer. The method used in this research is qualitative research with case study research which is then analyzed using comparative descriptive analysis. While data is collected through interviews and observations. After the data is collected, an analysis is carried out to find out the counseling process with rational emotive therapy and integrated with QS. Al-Hujurat verse 12, and compare between before and after the counseling process is carried out. The counseling process with Rational Emotive Therapy is done in steps: problem identification, diagnosis, prognosis, therapy, and evaluation. The results found that the client concerned has negative thoughts about the shape of his body, he is often upset and feel hopeless because his body is not ideal to achieve his desire to become a police officer. However, after guidance and therapy, the client feels that what he has perceived so far is wrong and intends to think rationally in the face of a problem. In the end, the client is motivated to achieve his goals by diligently exercising, learning to be grateful with the body that God gives, not complaining, maintaining diet and the client believes nothing is impossible if there is an effort from the heart.